2017
DOI: 10.24002/kinerja.v21i1.1034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of E-Service Quality on Customer Satisfaction and Loyalty Empirical Study in India Online Business

Abstract: Due to Globalization and advancement

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
3
29
2
7
Order By: Relevance
“…E-service quality is important to build customer loyalty because now onlinebased businesses have started to develop a lot; thus, e-service quality can determine customer loyalty. Based on the theory and supported by the research results of Asgari ( 2014), Cristobal et al (2007), and Sundaram et al (2017), it can be stated that e-service quality has a positive and significant influence on customer loyalty. H4: E-service quality has a positive and significant influence on customer loyalty.…”
Section: Loyaltymentioning
confidence: 86%
See 1 more Smart Citation
“…E-service quality is important to build customer loyalty because now onlinebased businesses have started to develop a lot; thus, e-service quality can determine customer loyalty. Based on the theory and supported by the research results of Asgari ( 2014), Cristobal et al (2007), and Sundaram et al (2017), it can be stated that e-service quality has a positive and significant influence on customer loyalty. H4: E-service quality has a positive and significant influence on customer loyalty.…”
Section: Loyaltymentioning
confidence: 86%
“…The existing literature on internet consumer behavior has not fully analyzed the benefits generated by higher perceived quality in terms of user satisfaction and loyalty. A research conducted by Sundaram et al (2017) stated that e-service quality significantly and positively influences customer loyalty. This research was conducted on e-commerce, aiming to test e-service quality with customer satisfaction and customer loyalty.…”
Section: Loyaltymentioning
confidence: 99%
“…Hal ini sejalan dengan penelitian dari Sundaram (2017) yang menunjukkan bahwa faktor kualitas layanan seperti responsiveness dan trust berpengaruh secara positif terhadap loyalitas secara langsung. Oleh karena itu, kualitas pelayanan online yang diberikan oleh perusahaan melalui website sangat penting untuk diperhatikan dan dijaga kualitasnya karena merupakan komponen utama bagi penyedia jasa online yang dapat mempengaruhi kepuasan dan loyalitas pelanggan.…”
Section: Pengaruh Positif E-service Quality Terhadap Loyalitas Pelangganunclassified
“…Sundaram et al in their study tested the conceptual framework of customer perception on service quality online business and its impact on satisfaction and loyalty through e-commerce business (Sundaram, Ramkumar, and Shankar 2017). Khan et al indicated that all the first latent constructs are significant where electronic customer satisfaction and e-customer loyalty are influenced by e-service quality.…”
Section: Role Of Service Quality In Customer Satisfactionmentioning
confidence: 99%